أسباب عزوف الطلبة عن دخول أقسام الرياضيات في الجامعات (Journal Of Educational and Psychological Researches, 2011)
The current study aimed to know the reasons for the reluctance ofstudents to apply mathematics department in the Iraqiuniversities. In order to achieve the objective of the study theresearchers a tool numbers of 4 - axes included 40 - paragraph,distributed as follows:- Set the first axis causes that relate to the student, the 14paragraph. - The second axis includes clauses concerning teacher and thenumber of paragraphs of Article 9, paragraph.- Axis III contains clauses concerning the nature of mathematicsand a number of paragraphs 11 paragraphs.- The fourth, which included reasons related to classmates andclose and the number of paragraphs 6, paragraph.The resolution offered on a group of arbitrators has beenamended some of the paragraphs and got the approval of 85% ofthe arbitrators on the affiliation of the paragraphs, which put intoit.Used psychometric properties of reliability and validity of themining and construction indicators endorsed the adoption of thepara-class correlation coefficient as extracted total consistencyby re-test (test-retest) and indicators were acceptable andstatistically significant at the5% level.Applied the questionnaire on a sample of the teaching staffnumbered around 20 by 10 pedagogy and teaching pedagogyfrom the University of Baghdad and 10 pedagogy and teaching ofthe University of Technology and took into account the differentlevels of scientific teacher assistant, teacher, professor, assistantprofessor.The sample was selected from students with 60 students by 30students from Baghdad University and 30 students, University ofTechnology was selected randomly from students and fromsections of the new mathematics in the education and scientificcollage.The results showed that the most common reasons unit is (asense of student rigid mathematics and its isolation fromdevelopment), and mathematics to deal with a banana so youneed from the student focus and mental effort significantly, hasalso developed some of the recommendations includingreconsideration of the decisions of the mathematics curriculum,and expand employment opportunities for graduates, and thedevelopment of teaching competence of teachers